Clinico-epidemiological study on canine toxicosis in Effurun/Warri Municipality region of Delta State, Nigeria - Kundu F. Shima; Aondover F. Gberindyer; Ternenge T. Apaa; Idusiye J. Mosugu (Journal of Advanced Veterinary and Animal Research, 2015)
The purpose of this study was to provide fundamental information on both the common toxicants and poisoning episodes in dogs within Effurun/Warri municipality region of Delta State of Nigeria from 2011 to 2014. The collected data were grouped according to age, sex, breed, year of occurrence, and toxicant type. The study revealed that a total of 76 dogs comprising 12 breeds were poisoned by several toxicants such as pesticides (69%; n=52/76), household products (12%; n=9/76), food and ndash;poisons (9%; n=7/76), and snakebite envenomation (3%; n=2/76). Mixed breeds (29%; n=22/76), Alsatian (25%; n=19/76), Rottweiler (16%; n=12/76) and indigenous breed (7%; n=5/76) ranked the topmost breeds accounted for most poison emergencies with human and ndash;related factors incriminated. This study provides useful information on episodes of poisoning in dogs in the studied region. The knowledge of agents involved can help veterinarians for accurate diagnosis, and pet owners to cautiously protect their pets from potentially poisonous substances. [J Adv Vet Anim Res 2015; 2(3.000): 357-361]